2013
DOI: 10.1371/journal.pone.0079080
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Ecology of Murinae (Muridae, Rodentia): A Geometric Morphometric Approach

Abstract: Murine rodents represent a highly diverse group, which displays great ecological versatility. In the present paper we analyse the relationship between dental morphology, on one hand, using geometric morphometrics based upon the outline of first upper molar and the dietary preference of extant murine genera, on the other. This ecomorphological study of extant murine rodents demonstrates that dietary groups can be distinguished with the use of a quantitative geometric morphometric approach based on first upper m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…The mouse tooth is one of the traits extensively studied regarding shape variation. In paleontology, it is a key character for phylogenetic and dietary inferences ( Misonne, 1969 ; Gómez Cano et al, 2013 ). It has been a model for developmental genetics ( Jernvall and Thesleff, 2012 ; Urdy et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The mouse tooth is one of the traits extensively studied regarding shape variation. In paleontology, it is a key character for phylogenetic and dietary inferences ( Misonne, 1969 ; Gómez Cano et al, 2013 ). It has been a model for developmental genetics ( Jernvall and Thesleff, 2012 ; Urdy et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis needs testing, since the diet of C. expulsus and C. tener has not been published in the literature. A study on the outline of the first molar of extinct murine rodents demonstrated that different diet groups could be distinguished through geometric morphometric analysis (Cano et al 2013). However, in marmots and some Didelphidae it has been demonstrated that diet is weakly correlated with molar shape (Caumul andPolly 2005, Chemisquy et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, GMM analyses require the manual acquisition of landmarks or outline data. In the case of the murine teeth, each molar occlusal view was manually delineated for the collection of the points along the outline, following a procedure applicable to different rodent taxa (Gómez Cano et al 2013;Ledevin et al 2010;Renaud et al 1996). The data acquisition for the ~1500 mice presented here therefore required, in total, several weeks of full-time fastidious work of an experienced operator.…”
Section: Deep Learning Algorithms As a Promising Tool For The Identifmentioning
confidence: 99%